Suplementação de vacas lactantes com gérmen integral de milho - Machado, Alan Soares (2014)
The purpose of this study was to evaluate the effect of replacing corn grain by integral corn germen in the diet for lactating cows using five levels of whole corn germ intake, on dry matter basis (0.0; 6.7; 13.5; 20.1 and 26.9 %) on dry matter intake, digestibility, ingestive performance, average particle size, non -degraded fraction, ruminal parameters, milk production and composition, feeding efficiency, energy concentration and lactation energy. In order to do so, five multiparous crossbred cows of 490 kg body weight were tested, 100 days after postpartum and averaging 26 Kg milk/day. Each experimental period lasted 21 days, with 13 days for adaptation to the diet and eight days for sample collection. Dry matter intake took place during the whole period of sample collection. To determine digestibility, a titanium dioxide external marker was placed directly into the rumen through a ruminal cannula and faeces were collected between the 16 and 18 days at each experimental period and. For the determination of the ingestive performance, on the 14 and 15 days, in five minute intervals, the events spent in leisure, ingestion and rumination. In DM and FDN analyses from the non-degradable fraction in situ, Tifton 85 hay was used at 24 and in 48 hours to check changes in ruminal environment. Milk production and samples for analyses of lactose, protein, ureic nitrogen and fat were collected on the 15, 17, 19, and 21 days of each experimental period. The experiment was arranged in a Latin square, and the variables apparent digestibility, ingestive performance, milk production and composition, ingestible dry matter, particle average size, non-degradable fraction, feeding efficiency, energy concentration, lactating energy and rum inal parameters were evaluated using polynomial regression. The regression models were subjected to analysis of variance considering the latin square design with test for lack of adjustment. The models where the regressors were significant and the lack of adjustment not significant were selected adopting the 5% level of significance. Pearson´s correlations were performed among all variables. Statistical analyses were performed using the software R. Ruminal liquid samples were collected manually at various sites of the rumen and filtered in gauze to determine pH, NNH3 and AGCC. The replacement of corn by whole corn germ did not cause any changes (P>0,05) in the ingestive performance , pH and N-NH3 . Milk production, protein content, lactose, protein:fart ratio and feeding efficiency increased (P<0.05), and a linear reduction (P<0,05) was observed in fat percentage and in energy concentration with lipids added to the diet. The diet with 26.9% of lipids added in the DM did not promote negative effect on the variables analyzed; suggesting that whole corn germ can be a substitute for corn in the diet of milking cows producing 26 Kg of milk.